Entrepreneurial university ecosystems and graduates' career patterns: do entrepreneurship education programmes and university business incubators matter? - GUERRERO CANO, MARIBEL; David Urbano; Eduardo Gajón (My University, 2020)
PurposeThis paper provides insights about how graduates' career patterns (i.e. academic entrepreneur, self-employed or paid employed) are influenced by entrepreneurial university ecosystems (i.e. incubators and entrepreneurship education programs).Design/methodology/approachBy adopting Douglas and Shepherd's utility-maximising function, the influence of one entrepreneurial university ecosystem on graduates' career choices was tested using a sample of 11,512 graduates from the Monterrey Institute of Technology and Higher Education (ITESM) in Mexico.FindingsOur results show the critical role of entrepreneurial universities ecosystems in facilitating employability options as academic entrepreneurship for ITESM's graduates. The study shows some insights about how graduates' risk aversion and work effort are positively influenced by the university business incubator and entrepreneurship education programs, respectively.Practical implicationsDiverse implications for stakeholders have emerged from our results. These implications are associated with potential benefits of implementing programmes oriented to engage academic entrepreneurship within Latin American universities.Originality/valueEntrepreneurial universities provide a range of employability alternatives for their students, such as to be self-employed, academic entrepreneurs or paid employees. In this scenario, entrepreneurial universities have configured entrepreneurial ecosystems (educational programmes, business incubators and other infrastructures) to support potential entrepreneurs (students, academics, staff and alumni). Despite the relevance of the environmental conditions on individuals' occupational choices, few studies have explored the role of the entrepreneurial university ecosystems on graduates' employability. In this vein, our study contributes to some academic discussions: (1) the role of context on career choice models (Ilougaet al., 2014; Sieger and Monsen, 2015), (2) the role of incubators and entrepreneurship education on fostering academic entrepreneurship on the graduates' community (Nabiet al., 2017; Goodet al., 2019; Guerrero and Urbano, 2019a) and (3) the effectiveness of the entrepreneurial university ecosystems on graduates' employability (Herreraet al., 2018; Wrightet al., 2017).
Keywords: academic entrepreneurship; emerging economies; entrepreneurial and innovation ecosystems; entrepreneurial university; graduates' career choice; university business incubation